OPTIMALISASI UNSUR LIVE SHOOT DAN MOTION GRAPHIC UNTUK PROMOSI DIGITAL LEMBAGA PAUD - Yulandina, Aldilla; Antoni, Condra; Firmanda, Ardiman (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2018)
Presentation of information for educational institutions is one of the most important means to introduce the institutions to the public. Raudhatul Athfal (RA) Ar-Rasyid Tanjungpinang needs media that can promote and provide information about the institution, because the number of registrants is decreasing during current years. This research was conducted with the creation of the institution’s profile video that applies elements of live shoot and motion graphics to easily convey information in short duration videos, and to make the profile video look interesting. The stage of making a profile video is starting from taking pictures directly (live shoot), editing to rendering process. Based on the process of designing, implementation, testing and discussion, it can be concluded that this research has been able to produce a profile video that can be used as a promotional mean for attracting new students in 2017/2018 at RA Ar-Rasyid Tanjungpinang. The result shows that 77% of 98 applicants have been informed through video profiles distributed with Videotron.